Transformasi Sosial dan Budaya Amerika Serikat dari Masa ke Masa - Alfin Nur Laila; Adzkiyak Adzkiyak (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
This article discussesthe social and cultural changes in the United States over time, with aspecial emphasis on the major changes that occurred from the 19th century to the modern era. There are a number of variables that have influenced social change in the United States, including the abolition of slavery, the civil rights movement, and the immigration process thathas resulted in a multicultural society. Influenced by a mix of European cultures, indigenous peoples, and immigrants from various parts of the world, the evolution of American culturehas produced a unique cultural wealth such as jazz, blues, and pop music. This transformation is also linked to changes in the economicand political spheres, which have impacted social structures, such as changes inlegislation and the expansion of individual rights. To describe the journeyand socio-cultural impact that reflects the complex and dynamic national identity of the United States, this article employs a qualitative literature review methodology. This article also examines the role of media and technology in accelerating and spreading socio-cultural change in American society.